Desirable qualities, attributes, and characteristics of successful athletic trainers - A national study - Henry, T. J.; Schneider, R. C.; Stier, W. F. (The Sport Journal, 2009)
In an effort to determine the importance of desirable qualities, attributes and characteristics necessary for the success of interscholastic athletic trainers a Likert-type scale survey was mailed to all head athletic trainers of NCAA Division III institutions in the United States. The survey consisted of 24 statements allowing for the following responses: essential, very important, important, not very important, and irrelevant. The qualities that were deemed the most desirable by head athletic trainers were trustworthiness (76.2%), honesty (73.5%), dependability (66.4%), and possessing high ethical standards (66.4%). The two characteristics that were found to be the least essential were being a risk-taker (2.1%) and being a visionary (6.4%).